Moduli of Reimann surfaces, real algebraic curves, and their superanalogs - Natanzon S M; Lando Sergei (Providence AMS, 2004)
The space of all Riemann surfaces (the so-called moduli space) plays an important role in algebraic geometry and its applications to quantum field theory. The present book is devoted to the study of topological properties of this space and of similar mod
Keywords: Algebraic curves; Riemann surfaces